Whether small and medium-sized enterprises in China should adopt Beyond Budgeting - Zhou, Fandi (2018)
Since the inception of the budgets in the 1920s, they have been deeply ingrained in the culture of business (Goode and Malik, 2011), and have historically played an essential role in the management control (Otley, 1994; Réka et al., 2014). However, recently they have become the subject of criticism and debate (Libby and Lindsay, 2010), some researchers thought that the budgeting could be improved (Horngren et al., 2004), while others argued the process of budgeting are fundamentally flawed (Neely et al., 2001; Hope and Fraser, 2003). In this paper, the author presents the study of the budgeting process in three enterprises in China, among which one is the private company and the others are two state-owned, to 1) update the literature on budgeting practice 2) collect empirical evidence to analyse the criticism about budgets. Overall, the author found that although problems exist with budgets, the budgeting system is still viewed as essential in the managerial control in these three companies, and these three enterprises do not need the Beyond Budgeting.